The Influence of Process Fluids on the Machining Process and Forming Internal Threads - Rejzek, Miroslav; Jersak, Jan; Votocek, Jaroslav (Manufacturing Technology Journal, 2016)
Using cutting or forming taps during the production of internal threads represents the basic method of manufacturing these coupling structural components, which - in the case of smaller dimension internal threads - can be encountered in many manufacturing processes. To optimize the cutting process and forming of internal threads, and in favour of the final results of these operations, the right choice of technological conditions, process fluids and methods of their application in areas where the technological process is realized, is needed. An important aspect of the use of process fluids are relatively large operating costs, and in some cases also the adverse environmental effects. Therefore, one of the current trends is reducing the amount of process fluids used during machining operations. At the Department of Machining and Assembly at the TU of Liberec experiments were conducted and various technological methods of production of internal threads during the use of various types of process fluids and methods of their application in the technological process were compared. During machining and molding, technological process, the parameters and properties of the produced internal threads were evaluated.
Keywords: thread machining; thread forming; process fluid; MQL method